Graphic Organizer as Strategy to Teach Extensive Reading on Non-Fiction for EFL Learners - Astried Damayanti (Yayasan Visi Intan Permata, 2019)
The research was conducted based on the teaching and learning Extensive Reading on Non-fiction for second-semester students of English Language Education Department of STKIP PGRI Trenggalek. The research was aimed to apply graphic organizer appropriate with the type of non-fiction passage. The graphic organizers utilized in the research were Keep-in-Time Sequence String for Chronological Order passage, Venn Diagram for Compare and Contrast passage and Character Traits for Description passage. The research was also intended to know the students’ comprehension of the passage after the utilization of graphic organizer and their response toward the use of a graphic organizer in learning extensive reading. The students’ comprehension was evaluated by summarization. They were assigned to summarize each passage based on the graphic organized arranged in the previous activity. Meanwhile, the attitude scale was used to know the students’ response during the utilization of graphic organizer in learning extensive reading. The score of the summarization revealed that the students’ reading comprehension was good. The average of their summarization was 81.67. Based on the result of the attitude scale, the students gave a good response toward the utilization of graphic organizer in learning extensive reading.